Hogs statistics, supply and disposition of hogs - Statistics Canada (Government of Canada, 2017)
This table contains 143 series, with data for years 2000 - 2012 (not all combinations necessarily have data for all years), and is no longer being released. This table contains data described by the following dimensions (Not all combinations are available): Geography (13 items: Canada;Eastern provinces;Newfoundland and Labrador;Prince Edward Island; ...); Supply and disposition of hogs (11 items: Total supply of hogs;Beginning inventory of hogs;Pig crop;Interprovincial imports of hogs; ...).